Pengaruh Pemberdayaan, Efikasi Diri dan Budaya Organisasi terhadap Kinerja Pegawai Dinas Perpustakaan Kota Sibolga - Leonard Harianto Marpaung; Elwadip Ardi Friska Hasibuan; Syarifullah S; Erika Sari Siregar (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
Problem of this study what is influence of  empowerment on performance. What is influence of self efficacy on performance. What is influence of  organization culture on  performance. What is influence  empowerment, self efficacy and  organization culture on   performance. The purpose of this study to determine and analyze the effect of  empowerment on   performance. Determine and analyze the effect of   self efficacy on  performance. Determine and analyze the effect of  organization culture on  performance. Determine and analyze the effect of   empowerment,  self efficacy and  organization culture on   performance.  Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate  empowerment variable has a positive and significant effect on performance.  self efficacy variable has a positive and significant effect on  performance. Organization culture variable has a positive and significant effect on performance.  empowerment, self efficacy and  organization culture variable has a positive and significant effect on   performance